2023
DOI: 10.1097/shk.0000000000002193
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Vasopressors for Septic Shock Patients: A Systemic Review and Network Meta-Analysis

Abstract: Background Septic shock is a distributive shock with decreased systemic vascular resistance and mean arterial pressure (MAP). Septic shock contributes to the most common causes of death in the intensive care unit (ICU). Current guidelines recommend the use of norepinephrine as the first-line vasopressor, while adrenergic agonists and vasopressin analogs are also commonly used by physicians. To date, very few studies have synthetically compared the effects of multiple types of vasoactive medications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Because the MAP increased only near that before lipopolysaccharide administration at a maximum dose of 6 U/min, the response to further increases in dose and blood pressure is unknown. Recent clinical investigations have reported that vasopressor combination therapy does not decrease mortality more than that associated with monotherapy (30) and that vasopressin in combination with norepinephrine does not decrease the mortality rates (31); however, in practice, vasopressin is often used in combination with norepinephrine, and its effect on microcirculation is unknown. In addition, vasopressin was administered after norepinephrine, and the response would have been different if vasopressin had been administered first.…”
Section: Discussionmentioning
confidence: 99%
“…Because the MAP increased only near that before lipopolysaccharide administration at a maximum dose of 6 U/min, the response to further increases in dose and blood pressure is unknown. Recent clinical investigations have reported that vasopressor combination therapy does not decrease mortality more than that associated with monotherapy (30) and that vasopressin in combination with norepinephrine does not decrease the mortality rates (31); however, in practice, vasopressin is often used in combination with norepinephrine, and its effect on microcirculation is unknown. In addition, vasopressin was administered after norepinephrine, and the response would have been different if vasopressin had been administered first.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, its β-1 adrenergic receptor activity can lead to cardiac arrhythmias, limiting its use [2]. In a recent systematic review and network meta-analysis on thirty-three randomized controlled trials (RCTs) comprising 4966 patients, DA was associated with the highest incidence of cardiac arrhythmia and a higher risk of 28-day mortality due to septic shock compared to the other vasopressors [20].…”
Section: Introductionmentioning
confidence: 99%